Cytologic-Enzymologic Diagnosis of Experimental Pneumonia Induced by Klebsiella pneumoniae Serotype II in Rats and Its Treatment with Free and Liposomal Enrofloxacin - (:unkn) unknown (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2013)
Enrofloxacin (ENR) rapidly localizes in eukaryotic cells in vitro but does not remain for prolonged periods, thereby reducing the ENR efficacy of defense against intracellular pathogens. Delivery of ENR in a liposome-encapsulated form may enhance its intracellular residence time. In this study, experimental pneumonia was induced in healthy and dexamethasone-treated rats using Klebsiella pneumoniae serotype II. Free and liposome-encapsulated ENR were injected intravenously into the infected animals at a dose of 7.5 mg/kg/day for 5 days. Samples of tissue, plasma and bronchoalveolar lavage (BAL) fluid were obtained at 1, 2, 3 and 4 days and 1, 2, 3 and 4 weeks after the first antibiotic treatment. All of the samples were evaluated cytologically, enzymologically, microbiologically and pathologically. It was determined that cytologic and enzymologic diagnoses of BAL fluid are not meaningful for evaluating the treatment of the experimental pneumonia in rats. However, it was established that the use of ENR in liposomal form at a dose of 7.5 mg/kg for 5 days is more effective than the free form both in the treatment of K. pneumoniae infections and in the prevention of recurrent infections. Liposome-encapsulated antimicrobial agents should provide another choice for antimicrobial therapy in the future, but further investigation must be completed before clinical use.
Keywords: Enrofloxacin; Experimental pneumonia; Klebsiella pneumoniae; Liposome; Rat; Treatment; GLYCOL-COATED LIPOSOMES; BRONCHOALVEOLAR LAVAGE; FRANCISELLA-TULARENSIS; RESPIRATORY-TRACT; CIPROFLOXACIN; EFFICACY; LUNG; ENCAPSULATION; INFECTION; MODELS